Clinical parameters and treatment outcome in patients of acromegaly: A retrospective analysis of 51 patients - Shahid Ahmed; Ahmed Tashfeen Ashraf; Muhammad Junaid Mushtaq; Zujaja Hina Haroon (Journal of the Pakistan Medical Association, 2022)
The aim of the study was to analyze the pattern of clinical presentation and management outcome in patients of acromegaly. It is a cross-sectional study based on the clinical records of 51 patients of Acromegaly. All the recorded clinical data was analyzed to see the pattern of clinical presentation and management outcome. IBM SPSS statistics version 22 was used for statistical analysis. The median age was 32 years. Twenty seven patients underwent surgery and 6 (22.2%) achieved remission. With pharmacological management, 35.8% patients achieved control of the disease with Octreotide LAR and 7.1% with cabergoline. Eighteen patients were treated with External Beam Radiation (EBR) and Stereotactic Radiosurgery (SRS). Remission rate has been 88.9% with SRS and 33.3% with EBR. The study shows higher prevalence of Growth Hormone (GH) secreting tumour in younger people and men. Remission rate was highest in patients treated with radiotherapy after partial response to TSS. Keywords: Acromegaly, trans-sphenoidal surgery, radiotherapy, Octreotide. Continuous...